Case Report: Successful liver transplantation after achieving complete clinical remission of advanced HCC with Atezolizumab plus Bevacizumab combination therapy - Chouik, Yasmina; Erard, Domitille; Demian, Hassan; Schulz, Thomas; Mazard, Tessa; Hartig-Lavie, Kerstin; Antonini, Teresa; Mabrut, Jean-Yves; Mohkam, Kayvan; Rode, Agnès; Merle, Philippe (Frontiers in Immunology, 2023)
Background: Atezolizumab plus Bevacizumab combination therapy has recently emerged as the new standard of care for unresectable HCC. Significant tumor burden reduction can be observed under that treatment, raising the question of liver transplantation (LT). The safety of another immune checkpoint inhibitor (ICI), nivolumab, is unclear in the pre-transplant setting. Method: We report the case of a 57-y old man, with initial unresectable multinodular HCC contraindicated to LT and locoregional therapies, who achieves complete tumor response after Atezolizumab/Bevacizumab, and subsequently underwent LT for liver failure. Results: Explant analysis revealed complete pathological response with no tumor remnant. The patient suffered from several post-operative complications but no HCC recurrence or biopsy-proven acute rejection occurred 10 months after LT. Conclusions: Atezolizumab/Bevacizumab therapy may enable complete pathological response of advanced HCC. Safety of prolonged treatment need to be assessed.